Diet quality in preschool children and associations with individual eating behavior and neighborhood socioeconomic disadvantage. The STEPS Study - Tarro Saija; Lahdenperä Mirkka; Vahtera Jussi; Pentti Jaana; Lagström Hanna (Academic Press, 2025)
A good quality diet in childhood is important for optimal growth as well as for long-term health. It is not well established how eating behaviors affect overall diet quality in childhood. Moreover, very few studies have considered the association of diet quality and a neighborhood socioeconomic disadvantage in childhood. Our aim was to investigate how diet quality is associated with eating behaviors and neighborhood disadvantage and their interaction in preschool age children in Finland. The participants were from the Steps to Healthy Development Study at age 2 y (n = 780) and 5 y (n = 653). Diet quality was measured with a short questionnaire on habitual food consumption and eating behavior was assessed with the child eating behavior questionnaire to indicate the child's eating style regarding food approach and food avoidance dimensions. Information on neighborhood socioeconomic disadvantage were obtained from the statistics Finland grid database. We found that diet quality was higher at 5 years compared to 2 years of age (p < 0.001). Food approach subscale, enjoyment of food, was positively associated with the diet quality (p < 0.001 for 2 and 5 y) while subscale desire to drink was negatively associated with the diet quality (p = 0.001 for 2 and 5 y). Food avoidance was negatively associated with the diet quality both at 2 and at 5 years of age (p < 0.001). A higher neighborhood disadvantage was negatively associated with the diet quality at the age of 2 years (p = 0.02), but not at the age of 5 years. Eating behavior had similar associations with diet quality both in affluent and deprived neighborhoods. Our results suggest that both the eating behavior and neighborhood disadvantage are, already in the early age, important factors when considering children's diet quality.